Impact of Medical Training Programs on Time-to-Fill Physician Vacancies at the Veterans Health Administration - Li, Yufei; Legler, Aaron; Tenso, Kertu; Garrido, Melissa; Pizer, Steven (Medical care, 2024)
The Department of Veterans Affairs (VA) provides the largest Graduate Medical Education (GME) training platform for health professionals in the United States. Studies on the impact of VA GME programs on physician recruitment were lacking. To examine the impact of the size of residency training programs at a VA facility on the facility's time-to-fill physician vacancies, and whether the impact differs by the socioeconomic deprivation and public school quality of the geographic area. We constructed an instrumental variable for training program size by interacting the facility clinicians share with the total training allocation nationally. Our evaluation used national data on filled physician vacancies in the VA that were posted between 2020 and 2021. The outcome evaluated was time-to-fill physician vacancies. Our explanatory variable was the facility-year level number of physician residency slots. For positions posted in 2020, an increase of one training slot was significantly associated with a decrease of 1.33 days to fill physician vacancies (95% CI, 0.38-2.28) in facilities in less deprived areas, a decrease of 1.50 days (95% CI, 0.75-2.25) in facilities with better public schools, a decrease of 3.30 days (95% CI, 0.85-5.76) in facilities in both less deprived areas and better public schools. We found similar results for positions posted in 2020 and 2021 when limiting time-to-fill to <500 days. We found that increasing the size of the residency program at a VA facility could decrease the facility's time-to-fill vacant physician positions in places with less socioeconomic deprivation or better public schools.